The role of plastic surgery in major trauma in the United Kingdom and workforce recommendations. Issue 5 (May 2021) - Hendrickson, Susan A.; Young, Katie; Gardiner, Matthew D.; Phillips, Georgina; Wallace, David L.; Hettiaratchy, Shehan; Giblin, Anna-Victoria
Summary: Introduction: The 22 major trauma centres (MTCs) in England were appointed in 2012 to provide care to severely injured patients despite variation in existing infrastructure, resources, culture and skillset. Six MTCs remain unsupported by a co-located plastic surgery department. We describe the plastic surgical major trauma workload in England, the plastic surgical workforce and skillset available in each centre, and suggest what plastic surgical skills are required in an MTC. Methods: A multi-centre, prospective cohort study was performed to collect operative workload data. Eleven MTCs in England submitted complete datasets. Workforce data were provided by the British Association of Plastic Reconstructive and Aesthetic Surgeons (BAPRAS). Results: Fifty-three percent ( n = 1582) of Trauma and Audit Research Network (TARN)-eligible patients admitted during the study period underwent at least one operation during their index admission. Of these, 14% ( n = 227) required plastic surgery. The majority of plastic surgical operative work involved the extremities: 62% of index procedures involved the lower limb and 38% involved the upper limb. The number of full-time plastic surgical consultants per MTC ranged from 1 to 22. Only 10 MTCs had at least one plastic surgeon with a primary interest in lower limb trauma. Conclusion: Plastic surgery contributes substantially to major trauma care and the majority of this workload relates to extremity trauma. However, there is significant variability in the size, accessibility and skillset of the workforce available. On the basis of these data, we suggest a plastic surgical skillset which should be represented in plastic surgical departments supporting an MTC.